DESIGN AND MANUFACTURING PROCESS OF SMALL SCALE WATER TURBINE BY USING RPRT FOR ENERGY HARVESTING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The stator single-phase to ground fault is one of the most common fault that a Generator will suffer. If such fault is neglected then there are chances of converting it into phase to phase fault. So there is need to detect and isolate the faulty part from the rest of the system as early as possible. Because of this, protection is very important otherwise there is shortage of power in our system. The proposed approach detects the ground fault by analyzing the direction, magnitude, and energy of leakage current, which is the difference of zero-sequence current fault component between the neutral and the terminal of Power-former. The aim of the study carried out was realizing 100% coverage of fault detection in internal &external fault protection for the stator winding of Power former.